Novel Multidrug-Resistant Enterococcal Mobile Linear Plasmid pELF1 Encoding vanA and vanM Gene Clusters From a Japanese Vancomycin-Resistant Enterococci Isolate - Hashimoto, Yusuke; Taniguchi, Makoto; Uesaka, Kazuma; Nomura, Takahiro; Hirakawa, Hidetada; Tanimoto, Koichi; Tamai, Kiyoko; Ruan, Genjie; Zheng, Bo; Tomita, Haruyoshi (Frontiers in Microbiology, 2019)
Vancomycin resistant enterococci is one of troublesome pathogens in clinical settings because of few treatment options. A VanA/VanM-type vancomycin-resistant Enterococcus faecium clinical isolate was identified in Japan. This strain, named AA708, harbored five plasmids. One of these plasmids migrated in the gel without S1 nuclease treatment, which was indicative of linear topology. We named this plasmid pELF1. Whole genome sequencing analysis (WGS) of the AA708 strain revealed that the complete sequence of pELF1 was 143,316 bp long and harbored both the vanA and vanM gene clusters. Furthermore, mfold analysis and WGS data showed that the left end of pELF1 presumably formed a hairpin structure, unlike the right end of pELF1. The results of the exonuclease assay showed that pELF1 was not digested by lambda exonuclease, indicating that terminal proteins were bound to the 5 end of pELF1, similar to the Streptomyces linear plasmids. The result of sodium dodecyl sulfate-polyacrylamide gel electrophoresis was also consistent with this result. In the retardation assay, the DNAs containing the right end of proteinase K-untreated pELF1 did not appear to move as well as the proteinase K-treated pELF1, suggesting that terminal proteins might be attached to the right end of pELF1. Palindromic sequences formed hairpin structures in the right terminal sequence of pELF1; however, the sequence similarity with the well-known linear plasmids of Streptomyces spp. was not high. pELF1 was unique as it possessed two different terminal structures. Conjugation experiments revealed that pELF1 could be transferred to E. faecalis, E. faecium, E. casseliflavus, and E. hirae. These transconjugants exhibited not only high resistance to vancomycin, but also resistance to streptomycin, kanamycin, and erythromycin. This implied that pELF1 had the ability to confer multidrug resistance to Enterococcus spp. simultaneously, which might lead to clinical threats.